Wpływ okresu eksploatacji na efektywność pracy oczyszczalni hydrofitowej w Małyszynie = Period of operation impact on the effectiveness of work constructed wetland in Małyszyn - Jakubaszek, Anita; Płuciennik-Koropczuk, Ewelina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the pollutant removal efficiency of organic and biogenic compounds from wastewater in constructed wetland in Małyszyn. The results of long-term monitoring of wastewater treatment operation show that the efficiency of removal of organic pollutants from wastewater was 72%. However, total nitrogen and total phosphorus removed from wastewater were on average 22.5 and 13.3%. It was also demonstrated periodically landward of previously deposited phosphorous.
Keywords: oczyszczanie ścieków; oczyszczalnie hydrofitowe; oczyszczalniaz poziomym podpowierzchniowym przepływem ścieków; wastewater treatment; treatment wetland; SS-HF subsurface horizontal flow